Effect of processing methods on the chemical composition of Vitex doniana leaf and leaf products - Osum, Frances I. (Food Sci Nutr, 2013)
Fresh leaves of Vitex doniana were subjected to different food processing methods such as drying, blanching and drying, fermentation of the leaf extract as well as blanching and fermentation of the leaf extract. The proximate composition, mineral and vitamin contents of the fresh and processed leaves were subsequently determined, using standard methods. The results shows that V. doniana leaf and products had the following ranges of proximate parameters: 0.07–17.29% protein, 1.85–6.33% fiber, 0.47–6.55% ash, 10.86–95.67% moisture, 0.05–1.29% fat, and 3.61–58.08% carbohydrate. The level of micronutrients detected were generally high and ranged as follows: minerals – Ca (13.38–59.50 mg/100 g), Fe (3.0–18.00 mg/100 g), Na (0.37–1.29 mg/100 g), and vitamins C (1.5–32.98 mg/100 g), A (54.6–3583.26 IU), E (3.11–53.36 mg/100 g), and B(2) (0.01–9.63 mg/100 g). However, the various processing methods used led to significant (P < 0.05) decrease of micronutrients in the extracts, while it caused significant (P < 0.05) increase in the protein, fat, and ash content of the oven‐dried sample.